PEDAGOGICAL, PSYCHOLOGICAL, AND PRAGMATIC FEATURES OF IMPROVING STUDENTS' SPEECH AND LINGUISTIC COMPETENCIES BASED ON EDUCATIONAL TASKS (TAMADDUN NURI JURNALI, 2024)
The scientific and methodological basis for the pedagogical, psychological, and pragmatic characteristics of improving students' speech and linguistic competencies through educational assignments has been substantiated to enhance linguo-pedagogical competencies.